Burning out during the practicum: the case of teacher trainees. Issue 3 (15th March 2016) - Kokkinos, Constantinos M.; Stavropoulos, George
Abstract : The purpose of the present study was to empirically examine the link between practicum-related stressors, perceived general practicum stress, personal variables (i.e. general and teaching self-efficacy, epistemological beliefs, conceptions about teaching and learning, and trait anxiety) and burnout dimensions in a sample of 174 Greek student teachers, immediately after the completion of their practicum. In addition, the study sought to identify the best predictive combination of the studied variables for each burnout dimension. Participants who reported high general practicum stress indicated moderate levels of emotional exhaustion, but low depersonalisation and high personal accomplishment. Statistically significant correlates of burnout dimensions were used in three regression analyses. Results revealed that emotional exhaustion and personal accomplishment were predicted by practicum workload, whereas depersonalisation was predicted by teachers' epistemological beliefs (i.e. learning process) and practicum-related stressors (i.e. meeting pupils' needs). The present study contributes to the limited body of existing evidence on burnout in student teachers. The results are discussed in terms of both theoretical and practical implications.